Five years after - Forstchen, William R. (The John Matherson series, 2023)
"Five years after The Final Day, the Republic of New America has all but collapsed into regional powers and the world at large is struggling to remain stable as regional conflicts ravage the post EMP landscape. After several years attempting to lead a quiet life, John Matherson receives the news that the President is dying from a possible assassination attempt, and is asked to step in to negotiate with what appears to be a new military power hidden in the wreckage of the world. Pulled back into the fray, John struggles to hold the tottering Republic together. Facing threats on multiple fronts, he races against time to stop another EMP attack on the former United States and China, putting years of progress at risk. With so much of his work under threat, John must find the strength within to start over, so that he can save the country and the people that he holds dear from even greater calamity"--